PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH INDUSTRI PERBANKAN SYARIAH DI KOTA PEKANBARU - WIRDAYANI WAHAB (Maqdis: Jurnal Kajian Ekonomi Islam, 2017)
The research theme is the concept of business According to Islamic economics. The purpose of research is to see the effect of service quality on customer satisfaction Islamic banks. The study was conducted in the city of Pekanbaru. Samples are as many as 200 customers. Research using multiple linear regression. The study found there is significant influence between service quality and satisfaction.